Peso corporal e fitase na digestibilidade verdadeira do fósforo no farelo de arroz integral para suínos - Lucca, Walter (2014)
Two studies were carried out in the Department of Animal Science, Federal University of Santa Maria, with the objective of determining the effect of body weight and phytase on the total true digestibility (DTVP) and endogenous phosphorus loss (PEL) of rice bran (RB) using linear regression technique. The sample was composed of 24 castrated pigs, being 12 animals with 13 ± 1 kg and 46 days old, and 12 animals with 57 ± 2.5 kg and 86 days old. The animals were divided into six treatments consisted of diets with three levels (5, 10 and 20%) of RB and two levels of phytase (0 and 750 FTU/kg-1). Semi-purified diets were used with inclusion of blood plasma as a source of amino acids and Ca:P ratio of 2:1. Ferric oxide was used as a fecal marker. The experiments were conducted in three periods of 12 days each, being 7 days for adaptation and 5 days for total collection of feces. The total amount of feed was calculated based on the lowest consumption and provided in four meals a day, while water was ad libitum. Between each 12 day-period a diet was provided during three days to meet the nutritional requirements of the animals. Pigs were housed in 24 cages with adjustable metabolisms according to their body weight. The room temperature was maintained at 22°Celsius, using air conditioners. The variables were subjected to analysis of variance using the effect of period, animal, treatments and interactions in the model. The average weight in the piglets did not change in relation to the phytase and the RB. On the other hand, the intake of dry matter DMI(g/d); excreted dry matter DME(g/d) and digestible dry matter DMD(%); ingested phosphorus PI(g/d); excreted phosphorus PE(g/d) and absorbed phosphorus PAbs(g/d) were significant by the level of RB and not significant the phytase, while the digestible the PD(%) was significant for phytase and RB. The DTVP and EPL of RB with and without the addition of phytase resulted 47.51% and 425.2mgP/kgDMI, R2=91% and 34.39% and 461.1 mgP/kgDMI, R2=97%, respectively. The addition of phytase in the diet reduced 6.76% the P excretion and the P coming from the RB reduced 38.46%. In the growth phase, live weight and DMI(g/d) the DME(g/d), DMD(%) and PI(g/d) and PAbs(g/d) were significant for RB. The PE(g/d) and PD(%) were influenced significant by phytase and RB. The DTVP and EPL of RB with and without phytase resulted 58.42% and 439.7mgP/kgDMI, R2 = 92.4% and 32.10% and 260.8mgP/kgDMI, R2 = 93.2%, respectively. There was a reduction of the PE with the addition of phytase in 27.92% and with the P coming from RB the reduction was 36.25%. The use of phytase in semi-purified diets with added RB promoted a reduction of fecal excretion of P in both studied weights and, consequently, there was an increase in the DTVP. However, the effect of the enzyme was more pronounced in higher body weight of pigs (38 vs 45%). Phosphorus levels in serum did not change in the studied time periods for either phases and RB is rich in P. Much of this P is in the form of phytate with low digestibility, thus phytase has a significant role in providing this mineral, contributing in the increase of RB nutritional value.